PANALISIS POTENSI BAHAYA DENGAN METODE HIRADC (HAZARD IDENTIFICATION, RISK ASSESMENT AND DETERMINING CONTROL) PADA PROYEK KONSTRUKSI PEMBANGUNAN GEDUNG - Syafwarman Galingging; Ahmad Bima Nusa (Universitas Islam Sumatera Utara, 2026)
This study aims to determine the type and level of risk in the construction activities of the HotelBuilding Project in Medan. This study was analyzed using the HIRADC (Hazard Identification, Risk Assessment and Determining Control) approach where risk identification is first carried out based on documents and field observations. From the existing risk identification, a risk assessment will be carried out to obtain the risk level with data obtained from the distribution of questionnaires. The results of the study there are 5 jobs observed in the Hotel Building construction project in Medan. A moderate risk level was found for lightweight brick masonry and plaster wall work, with a probability level of 2 and an impact level of 3. Furthermore, a high risk level was found for gypsum partition wall work and stair work, with a probability level of 3 and an impact level of 3. Meanwhile, an extreme risk level was found for glass masonry, with a probability level of 3 and an impact level of 4. These risk controls were applied to each worker and the project environment in general. The implementation of risk controls in the field was carried out in accordance with the established OHS work plan method. However, not all workers were using PPE in accordance with regulations.